A Comprehensive Comparison on Foam Behavior in the Presence of Light Oil and Heavy Oil. Issue 5 (7th June 2018) - Pang, Shishi; Pu, Wanfen; Wang, Chongyang
Abstract: Crude oil properties significantly affect foam behavior that is important to foam application in enhanced oil recovery. This study focused on the comparison on foam behavior in the presence of light oil and heavy oil. Foamability and foam stability, the bubble size, and the film thickness as well as the configuration of oil drops were fully investigated. Final results indicated that both the heavy oil and light oil increased the foamability of sodium dodecyl sulfate but decreased that of the amphoteric surfactant imidazoline. The positive effect of both light oil and heavy oil on foam stability was reconfirmed. However, heavy oil was more favorable to foam stability. The light oil may shorten the foam half‐life but prolong the foam drainage half‐life. The heavy oil was more effective in reducing the foam size and increasing the foam uniformity compared with light oil. According to the micrograph of foam, light oil was emulsified into quite small oil droplets, filling the plateau borders and lamellas. The heavy oil, in the form of far larger oil droplets, was mainly distributed in plateau borders only. The larger oil droplets resulted in the more stable foam, which was verified. Moreover, light oil (oil B) performed well in thickening the foam film, as did the heavy oil (oil A). But for the lightest oil (oil C), a thinning effect on the film was detected.